Language and Literacy Strategies for Indigenous Children: A Scoping Review - Guiberson, Mark; Vining, Christine B. (Seminars in Speech and Language, 2023)
The purpose of this scoping review was to describe the existent research on language and literacy strategies for Indigenous children and to establish the strength of strategies described. A scoping review was conducted to locate existent studies that described language and literacy interventions used with Indigenous children. The following electronic databases were searched: PsycINFO, ERIC, CINAHL Complete, Academic Search Premier, Education Source, and ASHAWire. Articles were managed and analyzed using Covidence, a web-based program for review research. Results were charted and a preliminary evidence map was created. Forty sources were identified that described language and literacy strategies for Indigenous children. Strength of strategy coding revealed 5 sources had compelling strength, 5 had promising strength, and 30 had lacking strength. Overall, there remains limited research describing language and literacy strategies for Indigenous children. A preliminary evidence map was created to chart each strategy and sources that included the strategy, and to indicate the highest strategy strength observed across sources. A discussion of compelling strategies as well as strategies that may be culturally responsive is provided.
Keywords: Indigenous; language; literary